Biomarkers of the Endocannabinoid System in Substance Use Disorders - Francisco Navarrete; María S. García-Gutiérrez; Ani Gasparyan; Daniela Navarro; Francisco López-Picón; Álvaro Morcuende; Teresa Femenía; Jorge Manzanares (Biomolecules, 2022)
Despite substance use disorders (SUD) being one of the leading causes of disability and mortality globally, available therapeutic approaches remain ineffective. The difficulty in accurately characterizing the neurobiological mechanisms involved with a purely qualitative diagnosis is an obstacle to improving the classification and treatment of SUD. In this regard, identifying central and peripheral biomarkers is essential to diagnosing the severity of drug dependence, monitoring therapeutic efficacy, predicting treatment response, and enhancing the development of safer and more effective pharmacological tools. In recent years, the crucial role that the endocannabinoid system (ECS) plays in regulating the reinforcing and motivational properties of drugs of abuse has been described. This has led to studies characterizing ECS alterations after exposure to various substances to identify biomarkers with potential diagnostic, prognostic, or therapeutic utility. This review aims to compile the primary evidence available from rodent and clinical studies on how the ECS components are modified in the context of different substance-related disorders, gathering data from genetic, molecular, functional, and neuroimaging experimental approaches. Finally, this report concludes that additional translational research is needed to further characterize the modifications of the ECS in the context of SUD, and their potential usefulness in the necessary search for biomarkers.